Study the Association of Nucleotide Polymorphisms in Platelet Receptor and Cytochrome P450 Genes with the Development of Resistance to Antiplatelet Drugs in Patients with Coronary Artery Disease - K. S. Semashchenko; T. S. Mongush; A. A. Kosinova; T. N. Subbotina; Y. I. Grinshtein (Рациональная фармакотерапия в кардиологии)
Aim. To study the association of nucleotide polymorphisms in platelet receptor and cytochrome P450 genes with the development of resistance to antiplatelet drugs in CHD patients.Material and Methods. The study included 243 patients diagnosed with CHD after coronary artery bypass surgery (CABG), including 140 patients in the acetylsalicylic acid (ASA) treatment group and 103 patients in the dual antiplatelet therapy (DAT) group. All patients were tested for platelet aggregation using an optical aggregometer with inducers: 5 mM ADP and 1 mM arachidonic acid (AA). DNA samples were analyzed by allele-specific PCR for the presence of polymorphisms rs2046934, rs1126643, rs5918, rs6065, rs4244285 in the platelet receptor and cytochrome P450 genes.Results. No statistically significant differences were found during comparison of the prevalence of the studied polymorphisms in the platelet receptor and cytochrome P450 genes between the groups of aspirin-sensitive and aspirin-resistant patients, as well as between the groups of clopidogrelsensitive and clopidogrel-resistant patients. No association between carriage of the minor and major alleles of the polymorphisms studied and the development of antiplatelet drug resistance was found. In the group of patients on ASA therapy, carriers of the C allele of the T1565C (rs5918) ITGB3 polymorphism had a higher rate of AA-induced platelet aggregation compared to carriers of the T allele (18,49±25,92 vs 10,43±17,34, р=0,004).Conclusion. Polymorphisms of P2RY12 (rs2046934), ITGA2 (rs1126643), ITGB3 (rs5918), GP1BA (rs6065), CYP2C19*2 (rs4244285) genes are not associated with antiplatelet drug resistance in both patients on ASC therapy and on DAT. The presence of minor alleles of the rs2046934, rs1126643, rs6065, rs4244285 polymorphisms are not associated with increased platelet aggregation activity before CABG.However, in the group of patients on ASA therapy C-allele carriers of the rs5918 polymorphism of the ITGB3 gene had a higher rate of AA-induced platelet aggregation compared to T-allele carriers.